ANALISA PENERAPAN PELAKSANAAN PPH 4 AYAT 2, PPH 21, DAN PPH 23 PT HAWLIR NABILA - WidyaPutra, Naufal; Widyasari, Widyasari (Jurnal Paradigma Akuntansi, 2024)
This study aims to determine whether the realization of the tax liability of Tax Article 4 Paragraph 2, Tax Article 21 and Tax Article 23 which applies in 2021, and the first quarter of 2022 in PT Hawlir Nabila is in accordance with the applicable law. Samples were taken by interview method with PT Hawlir Nabila as a resource person. This study aims to prove the discipline of PT Hawlir Nabila in cutting, counting, and reporting these three aspects. PT Hawlir Nabila is an entity that operates in the rental and real estate sector so that income from income Tax article 4 paragraph 2 is final, PT Hawlir Nabila also employs employees so that there is an object of income Tax article 21, and PT Hawlir Nabila also uses services from outside the company so that there is an object of Tax article 23. The results of this study prove that PT Hawlir Nabila and the tenant PT Hawlir Nabila have complied with the tax law concerning Tax article 4 paragraph 2, Tax article 21, and Tax article 23 in the in the period from 2021 to the first quarter of 2022. The implication of this research is PT Hawlir Nabila needs to pay attention to the latest tax laws in order to avoid sanctions.